FRI0621 ASSOCIATIONS BETWEEN ORGAN INVOLVEMENTS AND GENDER, ALLERGY, AND MALIGNANCY IN 166 PATIENTS WITH IGG4-RELATED DISEASE. (June 2019) - Yoshifuji, Hajime; Shirakashi, Mirei; Kodama, Yuzo; Chiba, Tsutomu; Yamamoto, Motohisa; Takahashi, Hiroki; Uchida, Kazushige; Okazaki, Kazuichi; Ito, Tetsuya; Kawa, Shigeyuki; Yamada, Kazunori; Kawano, Mitsuhiro; et al.
Abstract : Background: Symptomatic differences between male and female patients with IgG4-related disease (IgG4-RD) have been reported [1]. Associations between IgG4-RD and allergy and malignancy have also been reported, although they are controversial. Objectives: We previously analyzed the treatment course of IgG4-RD using a multi-center cohort [2]. In the present study, we investigated the associations between organ symptoms and gender, allergic diseases, and malignancies. Methods: Data of 166 patients with a definitive diagnosis of IgG4-RD were retrospectively analyzed. Results: The cohort consisted of 108 men (65%) and 58 women (35%). Most frequently, the submandibular gland (52%), pancreas (46%), lachrymal gland (43%), and lymph node (38%) were affected. Furthermore, we assessed the frequencies of female sex, allergy, and malignancy in patients with each affected organ (Table 1 ). The organs with high frequencies of women included the lachrymal gland (50%), lungs (44%), and submandibular gland (43%). Those with low frequencies of women included the thyroid gland (0%), retroperitoneum (17%), and para-aorta (19%). In addition, allergic diseases were found in 60 patients (36%) (Fig. 1A ). The organs with high frequencies of allergy included the thyroid gland (50%), submandibular gland (47%), and lachrymal gland (40%). Those with low frequencies of allergy were the para-aorta (13%), prostate gland (30%), and retroperitoneum (31%). Malignancies were found in 23 (14%) patients (Fig. 1B ). Organs with high frequencies of malignancy included the para-aorta (38%), prostate gland (30%), and retroperitoneum (21%). In comparison, those with low frequencies of malignancy included the thyroid gland (0%), lungs (8%), and kidney (8%). Conclusion: Craniocervical organ involvement was associated with female sex and presence of allergic diseases, suggesting that allergy may contribute to onset of IgG4-RD in some patients. Abdominal organ involvement was associated with male sex and presence of malignancies, suggesting that malignancy may in part contribute to IgG4-RD. Reference: [1] Wang, et al., Rheumatology, 2018. [2] Shirakashi, et al., Sci Rep, 2018. Disclosure of Interests: Hajime Yoshifuji: None declared, Mirei Shirakashi: None declared, Yuzo Kodama: None declared, Tsutomu Chiba: None declared, Motohisa Yamamoto: None declared, Hiroki Takahashi: None declared, Kazushige Uchida: None declared, Kazuichi Okazaki: None declared, Tetsuya Ito: None declared, Shigeyuki Kawa: None declared, Kazunori Yamada: None declared, Mitsuhiro Kawano: None declared, Shintaro Hirata Grant/research support from: Eli Lilly, UCB, Consultant for: Bristol-Myers Squibb, Jansen, UCB, Paid instructor for: AbbVie, Eisai, Tanabe-Mitsubishi, Speakers bureau: AbbVie, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eisai, Eli Lilly, Jansen, Kissei, Pfizer, Sanofi, Takeda, Tanabe-Mitsubishi, UCB, Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics, Masafumi Moriyama: None declared, Seiji Nakamura: None declared, Terumi Kamisawa: None declared, Shoko Matsui: None declared, Hiroto Tsuboi: None declared, Takayuki Sumida Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, Motoko Shibata: None declared, Hiroshi Goto: None declared, Yasuharu Sato: None declared, Tadashi Yoshino: None declared, Tsuneyo Mimori: None declared